Ocular complications in course of idiopathic retroperitoneal fibrosis - Zatorska, Barbara; Pojda-Wilczek, Dorota; Herba, Ewa; Pojda, Stefan (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Idiopathic retroperitoneal fibrosis is a rare collagen vascular disease of still unclear, immunological etiology. One of the first descriptions of this pathology was derived from Ormond and the Ormond's disease became its second name. It is characterized by a chronic, non – specific inflammation of the retroperitoneum, which obstructs retroperitoneal structures. The most frequent complication is the ureteric obstruction with hydronephrosis and renal failure. The fibrotic process may develop in different, even remote sites, including ophthalmic system. We have presented a 50-year-old woman with Ormond's disease and anterior uveitis. We have also described the other ocular complications of this disease.